Rancangan Program Pelatihan Untuk Meningkatkan Pengetahuan Ibu Mengenai Cara Mengembangkan Self Esteem (Harga Diri) Anak Usia 6-8 Tahun - Titin Florentina Purwasetiawatik (Jurnal Ilmu Pendidikan (JIP) STKIP Kusuma Negara, 2017)
Self esteem is the foundation of a child well being and a key to their success when they become adults. Based on assessment results, the researcher was interested in designing training program aimed to improve mother’s knowledge and comprehension about ways to develop self-esteem of 6-8 years old children. The basic theories in this research were theories of self esteem from Susan Harter (1999) in Mruck (2006) and Self Esteem: The Foundation of Good Behavior (Sears and Sears, 1995). The training program was designed using Development Training Program approaches (Kohls, 1995) with andragogy learning methods. The training tryout was designed using one group pre test - post test. Subjects of the training tryout were seven 36-40 years old mothers who had children in 1st – 3rd grade of elementary school. Subject’s educational backgrounds varied from senior high school to University graduates. Measurements were done using objective tests and observation during training process. Hypothesis were tested using Wilcoxon Signed Rank Statistic Test. The research results showed an increasing of mother’s knowledge about self-esteem basic concepts and about ways to improve children’s self esteem with estimated value of 12,17%. That was a significant improvement (p = 0.018 <? = 0.05). The increased knowledge of each subject was about 6% to 26% in 1st dimension, and about 2% to 23.92% in 2nd dimension. Thus, it’s concluded that the design of training program to develop self-esteem of 6-8 years old children did increase mother’s knowledge.